Exploring Student Assessment Practices in Vietnamese Teacher Training Universities through Naturalistic Inquiry (Journal of Contemporary Educational Policies and Practices, 2025)
Qualitative research has gained increasing attention in Vietnamese education, yet the application of Naturalistic Inquiry to study educational assessment practices remains relatively underexplored. This ethnographic study investigates the beliefs, values, and attitudes of lecturers and academic managers toward student assessment practices in Vietnamese teacher education universities, employing Lincoln and Guba’s (1985) Naturalistic Inquiry paradigm. Through in-depth interviews and document analysis, the research uncovers a spectrum of perspectives - from traditional, summative-focused approaches to reform-oriented, formative practices - shaped by institutional, cultural, and personal factors. The findings highlight the tension between entrenched norms and emerging progressive ideals, offering insights into how these dynamics influence assessment practices critical to teacher education. By demonstrating the methodological rigor of Naturalistic Inquiry through its operational characteristics and trustworthiness criteria, this study not only enriches understanding of student assessment practices within Vietnam’s educational context but also offers novice researchers a practical model for applying this approach in educational studies.
Keywords: Student assessment; naturalistic inquiry; trustworthiness; teacher training universities; Vietnam